Coaches` internal model of the tennis serve technique: Knowing or understanding? - Fetisova, Y.; Zois, J.; Spittle, M.; Dawson, A. (International Journal of Sports Science & Coaching, 2021)
The understanding of coaches` knowledge plays a critical role in coach development. This study aimed to examine the internal models of expert and novice tennis coaches and to identify the key distinguishing characteristics between levels. Data was captured by in-depth interviews and analysed using a combination of qualitative and quantitative methodologies. The results revealed that the internal model consisted of seven components including the "functionality" component that has not been reported previously. A significant difference was detected only in three components of the internal model: "reasoning chains", "concepts" and "key flexion points". The findings led to the conclusion that the main attribute of tennis coaching expertise is not pure technical knowledge but rather the perception of technique as a whole movement and the ability to understand the connection between technical elements. The findings provide a valuable contribution to tennis coach development as it can be applied in coach education to facilitate novice coach development processes.